Effect of Health Lecture using Media and Peer-Education on Long Acting and Permanent Methods of Contraception - Helen Ermalia; Jimmy Yanuar Annas; Samsriyaningsih Handayani (Jurnal Ners, 2019)
Introduction: Long-acting and permanent methods of contraception (LAPMs) are known as highly-effective contraception. The Department of Health of East Java Province stated that LAPM participation is still below target. One of the factors is the Interpersonal Communication (IPC) skill of the Health Practitioners. This study aimed to identify the influence of health lectures using media and peer-education on the knowledge and attitude of pregnant women regarding LAPMs. Peer-education is the novelty of this study.Methods: A two-group quasi experimental design was applied with all of the pregnant women at Kesugihan Public Health Center (PHC) as the treatment group. They were given lectures with media inclusion (contraception booklets and visual aids) and peer-education during a pregnancy class. Pregnant women at Ngebel PHC were the control group. One woman who had experience with LAMPs was trained as a peer-educator. Thirty participants in each group were chosen using the total sampling technique. The data collected was analyzed using univariate and bivariate analyses by applying the Wilcoxon Signed-Rank and Mann-Whitney tests.Results: The participants showed an increased knowledge before and after the intervention in the treatment group (83%), while in control group, it was slightly increased (1%). Attitude differences were also found in both groups (treatment = 56.7%, control = 13.3%). The Mann-Whitney test resulted in significant differences on knowledge (p <0.001) and attitude (p = 0.016) between the two groups.Conclusion: The local department of health may optimize IPC using media and peer-education to improve the knowledge and attitude of pregnant women regarding LAPM participation.